Case Report: Surgical treatment of type B aortic dissection in an adult with double aortic arch - Luo, Chong; Bian, Longrong; Liang, Weitao; Wu, Zhong (Frontiers in Cardiovascular Medicine, 2024)
BackgroundDouble aortic arch (DAA) with type B aortic dissection in adults is a rare aortic vascular disease. The abnormal anatomical structure of the aortic arch in such patients presents significant challenges in the selection of surgical approaches, and there is a notable lack of exploration into endovascular repair approaches that simultaneously preserve asymptomatic vascular rings.Case descriptionA 43-year-old female patient was admitted due to recurrent chest and back pain lasting for over a month. Computed tomography angiography (CTA) indicated a double aortic arch anomaly with localized dissection of the descending aorta. Esophagography with barium swallow revealed vascular indentation on the upper and middle thoracic esophagus, with mild to moderate local narrowing. Based on a comprehensive preoperative evaluation of the imaging and the patient's clinical history, a thoracic endovascular aortic repair (TEVAR) procedure was performed. Considering that the deformity did not cause any clinical symptoms and that the vessel diameter and distance from the proximal anchoring area were sufficient, the posterior section of the dominant arch was chosen as the proximal anchorage zone, and a stent with proximal bare zone was deployed to maintain blood flow to the distal non-dominant arch and preserve the integrity of the vascular ring. Follow-up CTA scans at one- and six-month post-operation showed that the aortic stent was well-positioned, with no visible primary lesion. The patient reported complete resolution of chest pain and no difficulties with swallowing or breathing.ConclusionIn adult patients with DAA complicated by aortic dissection, the abnormal anatomy of the aortic arch poses significant challenges in making treatment decisions. After a comprehensive, multidimensional evaluation of the patient's medical history, CTA, and esophagography, we successfully performed TEVAR procedure. This case provides new insights into the surgical strategy for treating such rare conditions.